The Benefit of Mean Auditors: The Influence of Social Interaction and the Dark Triad on Unjustified Auditor Trust - Hobson, Jessen L.; Stern, Matthew T.; Zimbelman, Aaron F. (Contemporary Accounting Research, 2020)
ABSTRACT Regulators and researchers have expressed concerns that social interaction leads auditors to unjustifiably trust managers, constituting a lack of sufficient professional skepticism. Using both an abstract laboratory experiment and a contextually rich experiment with practicing auditors we predict and find that higher Dark Triad auditors (those with higher levels of the shared core between psychopathy, narcissism, and Machiavellianism) are relatively more resistant to lapses in professional skepticism due to the effects of social interaction. This is likely driven by higher Dark Triad auditors' callousness, lack of empathy, and lack of response to social stimuli. In contrast, while higher social interaction initially increases lower Dark Triad auditors' unjustified trust in managers, this effect reverses in subsequent interactions when lower Dark Triad auditors observe evidence suggesting managers have reported aggressively. These findings add to research on the effect of auditor personality traits, audit‐client social interaction, and the interaction of these two variables, and suggest that practitioners and researchers account for the interplay of Dark Triad traits and social interaction and their effect on professional skepticism.